Improving the Skills of Junior High School Mathematics Teachers in Developing Deep Learning-Oriented Lesson Plans Using ChatGPT - Rosyidi, Abdul Haris; Setianingsih, Rini; Hanifah, Umi; Masriyah; Ismail (Universitas Negeri Surabaya, 2026)
Advances in artificial intelligence (AI) technology offer significant opportunities for education to create more innovative and adaptive learning experiences. Mojokerto Regency, East Java, with over 100 junior high schools, faces challenges in integrating modern technology into learning, particularly in mathematics. These challenges include teachers' limited understanding of AI technologies such as ChatGPT, limited resources, and limited access to technology-based training. This study aims to describe the improvement of junior high school Mathematics teachers' understanding and competency in developing deep learning of lesson plans using the ChatGPT after participating in technology-based training. This study was conducted through training on an introduction to AI (ChatGPT), discussions on the ChatGPT-assisted deep learning of Mathematics lesson plans and mentoring in developing the ChatGPT-assisted deep learning of Mathematics lesson plans. Participants were given a pretest before the activity and a post test after the training. Furthermore, participants were assessed as a group on their performance in developing the ChatGPT-assisted deep learning Mathematics lesson plan. Based on the results of the pretest and posttest analysis, and group performance, it can be concluded that there is an increase in the understanding and competence of Mathematics teachers in using AI (ChatGPT), to develop a deep learning of lesson plan that is interactive, relevant, and supports the implementation of the Merdeka Curriculum